INTERPOLATION SEARCH - Apeināns, Dzintars; Steklovs, Vasilijs; Grabusts, Pēteris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Searching for information may take some time because of slow searching algorithm work. Some of searching algorithm work comparing needed value with all array's value of step by step. In this work will be looking about interpolation search which predict looking value place in array. Main idea is to compare searching algorithm by time which it take to find correct value and will make conclusions which of compared algrithm work faster with different size of array.